2007
DOI: 10.1213/01.ane.0000219586.65112.fa
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Antinociceptive Efficacy of Intrathecal and Epidural Contulakin-G in Rats and Dogs

Abstract: Contulakin-G is a novel conopeptide with an incompletely defined mechanism of action. To assess nociceptive activity we delivered Contulakin-G as a bolus intrathecally (0.03, 0.1, 0.3, 3 nmol) or epidurally (10, 30, 89 nmol) in rats. Intrathecal Contulakin G significantly decreased Phase II and, to a lesser degree, Phase I paw flinching produced by intradermal formalin. Intrathecal and epidural doses of ED50s were 0.07 nmol and 45 nmol, respectively, giving an epidural/intrathecal ED50 ratio = 647). In dogs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…In contrast, in this study, morphine induced higher degree of hyperthermia in freely moving rats, and it reached its peak effect (about 1.8°C increase) at 1 μg, a dose without antinociceptive properties (Martin & Naruse, 1982). Another study has showed that morphine caused a U-shape dose-response curve (11.25-90 μg), where the lower doses have resulted in higher degree of hyperthermia (Martin & Naruse, 1982), but other studies have found that IT morphine did not influence the rectal temperature in rats (10 μg) or in dogs (170 μg) (Allen et al, 2007;Fukazawa et al, 2005). These data indicate that the applied doses, the route of administration or the level of stress may greatly affect thermoregulatory responses to opioids.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, in this study, morphine induced higher degree of hyperthermia in freely moving rats, and it reached its peak effect (about 1.8°C increase) at 1 μg, a dose without antinociceptive properties (Martin & Naruse, 1982). Another study has showed that morphine caused a U-shape dose-response curve (11.25-90 μg), where the lower doses have resulted in higher degree of hyperthermia (Martin & Naruse, 1982), but other studies have found that IT morphine did not influence the rectal temperature in rats (10 μg) or in dogs (170 μg) (Allen et al, 2007;Fukazawa et al, 2005). These data indicate that the applied doses, the route of administration or the level of stress may greatly affect thermoregulatory responses to opioids.…”
Section: Discussionmentioning
confidence: 98%
“…Several human studies have reported on core temperature changes after spinal opioid administrations, but only a few animal studies have investigated the role of spinal opioid receptors in this respect (Dib, Cormareche-Leydier, & Cabanac, 1982;Martin & Naruse, 1982;Rudy & Yaksh, 1977;Ryan, Price, Warriner, & Choi, 2012;Smith, Welch, Dombrowski, & Dewey, 1993). These studies investigate restrained animals and/or the thermistor is introduced into the colon causing significant stress responses, which leads to modified thermoregulation and motor behavior (Allen et al, 2007;Fukazawa et al, 2005;Martin & Naruse, 1982;Rudy & Yaksh, 1977). Sympathetic preganglionic neurons activated by glutamate via NMDA receptors also influence the core temperature (LoPachin & Rudy, 1982Rudy & Yaksh, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ziconotide (Prialt®), the synthetic equivalent of ω-MVIIA from the venom of C onus magus , a potent and selective blocker of the Ca V 2.2 calcium channel, is being used to treat chronic pain (Miljanich, 2004). Some of the hormone/neuropeptide-like components of Conus venom also show similar therapeutic potential: contulakin-G, a neurotensin analogue from the venom of C. geographus , is a potent analgesic (Allen et al, 2007) and at one point had progressed as far as human clinical trials. Further exploration of this group of venom components may offer an exciting new avenue for the discovery of novel pharmacological tools and drug candidates, complementary to conotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…It has significant sequence similarity to human neurotensin and acts as an agonist at the neurotensin receptor 1 GPCR albeit with significantly lower affinity than the endogenous human ligand [79,81]. Contulakin-G (CGX-1160) and its non-glycosylated analog (CGX1063) are potent analgesic agents effective in several animal models of chronic and acute pain (intrathecal, epidural or intraplantar administration) and also have antipsychotic and anticonvulsant activities when delivered via the intracerebroventricular route [81,82]. All analogs showed motor impairment effects at higher doses, suggesting a relatively narrow therapeutic window [81].…”
Section: Contulakin Gmentioning
confidence: 99%